Experimental and molecular dynamics simulation studies on thee solubilityof amino acids in aqueous electrolyte solutions - Tomé, L.I.N. (2014)
Separation and concentration of biological compounds are current subjects of interest due to their high cost in comparison to the total manufacture cost. For that purpose electrolytes may be employed as they can effect significantly biochemicals solubilities, a feature that has been used for salt-induced precipitation of proteins.